2015
DOI: 10.1002/joc.4601
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale patterns of daily precipitation extremes on the Iberian Peninsula

Abstract: The study of weather extremes is critical because of their great impact on the environment, economy and society. The identification of areas at greater risk of extreme conditions, and of meteorological situations that give rise to such conditions, enhances the understanding of climate risks and helps establish measures to reduce adverse impacts. In the current paper, precipitation extreme events (PEEs) in Spain between 1960 and 2011 were analysed. Thresholds for determining event severity were defined using 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 72 publications
10
57
0
Order By: Relevance
“…Some previous works in Spain that used a lower spatial resolution and a lower number of observatories (Herrera et al, 2012;Merino et al, 2015) showed overestimated values in extreme precipitation indices in some areas (especially in the north-west area of the Iberian Peninsula) but smoothing in others (e.g. Central Range).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some previous works in Spain that used a lower spatial resolution and a lower number of observatories (Herrera et al, 2012;Merino et al, 2015) showed overestimated values in extreme precipitation indices in some areas (especially in the north-west area of the Iberian Peninsula) but smoothing in others (e.g. Central Range).…”
Section: Discussionmentioning
confidence: 88%
“…But they are also suitable to analyse spatial patterns in daily characteristics of precipitation through extreme indices that allow comparisons between regions. In Spain, these indices have been applied to mainland Spain (Martín-Vide, 2004;Herrera et al, 2012;Merino et al, 2015) and to specific regions (Casas et al, 2007;Martínez et al, 2007;Rodrigo and Trigo, 2007;Lopez-Moreno et al, 2010). All of these datasets used the precipitation estimations to compute climatic indices.…”
Section: Or Wildfiresmentioning
confidence: 99%
“…The most severe events are mainly associated with flash floods that are often produced by a sudden thunderstorm that usually develops into a mesoscale convective system. In addition, [26] studied the large-scale patterns of daily precipitation extremes on the Iberian Peninsula, where it was found that extreme precipitation events on the Western Iberian Peninsula mainly occurred under strong zonal flow, with a long Atlantic fetch generating moisture advection towards that area. On the eastern sector of the Iberian Peninsula, the most important pattern associated with extreme precipitation is characterized by a cut-off low system at mid-levels together with easterly moisture flow from the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Cortesi et al (2012) assessed the statistical structure of daily precipitation over Europe from 1971 to 2010 using the daily precipitation concentration index (CI), suggesting significant positive trends in most of observatories south of Spain and along the Mediterranean coasts. More recently, Merino et al (2016) defined regions that exposed to extreme precipitation hazards over the Iberian Peninsula and assessed trends of extreme precipitation index from 1960 to 2011, based on the 99 th percentile of daily precipitation distribution.…”
Section: Changes In Daily Extreme Precipitationmentioning
confidence: 99%